PENYAJIAN DATA SURVEI DARING TERHADAP FENOMENA WANITA BEKERJA DARI RUMAH SELAMA PANDEMI COVID-19 - Farah Kristiani; Tutik Rachmawati; Anne-Marie Hilsdon (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
ABSTRACTThe global COVID-19 pandemic, particularly in Indonesia, has led many businesses and institutions to ask their staff to work from home. This policy has had a significant impact on female employees, especially those who are already married, because at the same time, educational institutions from elementary to higher education have also implemented a Distance Learning (PJJ) policy. These female employees were frequently required to make changes and divisions of tasks. This paper presents data from an online survey regarding the work and household aspects that affect female employees' performance during Work from Home. Adding to that is information on the type of assistance provided by the company/institution to help them enhance their performance productivity. According to the results of this online survey, 52.3 percent of respondents said their productivity has declined due to numerous work and household variables. Furthermore, the supporting variables that are expected to improve their performance productivity are mentioned. These bolstering variables were gathered from 47.7% of respondents who said their productivity had increased. By understanding these supporting variables, the company/institution would gain insight into how to change the policies that must be applied to their female employees to improve their productivity when working from home.Keywords: female worker; COVID-19; working from home; productivity; online surveyABSTRAKSituasi pandemi COVID-19 di seluruh dunia dan khususnya di Indonesia memaksa banyak perusahaan/institusi mewajibkan karyawannya bekerja dari rumah. Kebijakan yang diterapkan ini membawa dampak besar bagi para karyawan perempuan khususnya yang sudah berumah-tangga karena dalam waktu yang bersamaan, insitusi pendidikan sekolah dasar sampai pendidikan tinggi juga memberlakukan kebijakan Pembelajaran Jarak Jauh (PJJ). Banyak penyesuaian waktu dan pembagian kerja yang terpaksa dilakukan oleh para karyawan perempuan ini. Tulisan ini menyajikan data hasil survei daring mengenai faktor-faktor pada aspek pekerjaan dan rumah tangga yang mempengaruhi produktifitas kinerja para karyawan perempuan selama mereka menjalankan kebijakan Bekerja dari Rumah. Pemaparan data dilengkapi juga dengan informasi mengenai jenis dukungan dari perusahaan/institusi sehingga dapat meningkatkan produktifitas kinerja mereka. Dari survei ini diperoleh data bahwa 52,3% menyatakan bahwa produktifitas mereka menurun karena berbagai faktor dari aspek pekerjaan dan rumah tangga. Selanjutnya, diuraikan juga faktor-faktor pendukung yang diharapkan dapat meningkatkan produktifitas kinerja mereka. Faktor-faktor pendukung ini dikumpulkan dari 47,7% responden yang menyatakan bahwa produktifitas kinerja mereka meningkat. Diharapkan dari pemaparan faktor-faktor pendukung ini, pihak perusahaan/institusi mendapatkan informasi sebagai masukan agar dapat menyesuaikan kebijakan yang harus diberlakukan pada karyawan perempuan mereka agar produktifitas kinerja mereka bisa meningkat selama mereka harus Bekerja dari Rumah.Kata kunci: karyawan perempuan; COVID-19; bekerja dari rumah; produktifitas; survei daring